2020
DOI: 10.1002/jum.15281
|View full text |Cite
|
Sign up to set email alerts
|

Can Point Shear Wave Elastography Be Used as an Early Indicator of Involvement?

Abstract: ObjectivesThe aim of this study was to determine the effect of cystic fibrosis (CF) on pancreas and liver elasticity in young children using point shear wave elastography and to determine the relationship with clinical findings.MethodsTwenty‐two patients with genetically proven CF, who were admitted to our pediatric gastroenterology clinic, and 22 healthy control participants were enrolled in the study. The shear wave velocity (SWV) of the liver and pancreas were measured with point shear wave elastography.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…reported increased liver stiffness in paediatric patients with CF over time and patients with further increase in liver stiffness progressed to CFLD. In liver elastography studies by Sağlam et al 10 . in 19 CF patients and control subjects, significantly increased liver stiffness values were observed among patients with CF compared to healthy children.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…reported increased liver stiffness in paediatric patients with CF over time and patients with further increase in liver stiffness progressed to CFLD. In liver elastography studies by Sağlam et al 10 . in 19 CF patients and control subjects, significantly increased liver stiffness values were observed among patients with CF compared to healthy children.…”
Section: Discussionmentioning
confidence: 94%
“…Studies on adult patients have found that US and magnetic resonance imaging elastography methods can detect liver fibrosis with high accuracy rates 7,8 . However, since paediatric patients less frequently present with clinical manifestations of hepatic involvement, the role of elastography in this setting has been investigated in only a few studies 9,10 …”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…While all three techniques can be applied for spleen examination, pSWE and 2D‐SWE are preferred for the evaluation of the pancreas, kidney, gastrointestinal system, and other organs 12 . Studies on pancreatic elastography involving pediatric and adult CF patients are limited in the literature 8,13 . It may be important to observe pancreatic elasticity early in young patients with CF and to detect pancreatic insufficiency by elastography.…”
mentioning
confidence: 99%
“…12 Studies on pancreatic elastography involving pediatric and adult CF patients are limited in the literature. 8,13 It may be important to observe pancreatic elasticity early in young patients with CF and to detect pancreatic insufficiency by elastography.…”
mentioning
confidence: 99%